Assertion and Restraint in Dhamma Transmission in Early Pali Sources - Dixon, Graham (Buddhist Studies Review, 2015)
The study seeks to elucidate the nature of early Dhamma-transmission. While Buddhism has achieved broad geographical dissemination, sometimes earning the epithet ‘missionary’, Pali sources are ambivalent regarding approaches to potential followers. The Buddha’s final words do not instruct the sangha to spread the message; the exhortation, ‘walk, monks … for the blessing of the manyfolk’, rather appears to be an early, isolated episode. The Buddha’s own hesitation to teach provides the paradigm for the renunciant sangha, whose members rarely initiate teaching episodes, preferring to wait for specific questions, an approach still formalised in modern practice. Following brahmanical norms, excessive eagerness to communicate would have devalued the message. Capacity to understand varied between individuals, and intelligent questions indicated preparedness. Given the dependence upon lay-followers, the alms-round ensured regular sangha visibility. Embodied serenity, closely regulated by the Vinaya, both excited curiosity and proved beneficial to onlookers – an affecting darsana. Frequently dana, meal offerings, provided the locus for communicating Dhamma in a graduated, step-by-step manner, according to the capacity of the listeners. Kindness and generosity thus provided the point of departure, while miraculous displays were generally eschewed. In the proposed model, the alms-round is viewed as being undertaken to occasion generosity, making available a merit-field to generate benefits for the givers, rather than promotionally. The infrequent hints of greater assertion are confined to lay-followers, who, building on friendships, may occasionally draw attention to Dhamma. Arguably, this complements the role of the renunciant sangha, the guardian of the tradition, for whom teaching was not in fact obligatory. Though some lay-followers instructed others, their practice focussed on generosity and devotion. Some commentators have suggested that the original zeal waned over the centuries. However, the broadly reticent approach emerges as authentic in underlining the importance of the teachings, valuing goodness in other traditions, and accepting progression across multiple lifetimes. Most significantly, it underlines that coercion sits uneasily within a tradition which insists on exploration and personal transformation.